Chicken-manure-derived biochar reduced bioavailability of copper in a contaminated soil - Meier, Sebastián; Curaqueo, Gustavo; Khan, Naser; Bolan, Nanthi; Cea, Mara; Eugenia, González María; Cornejo, Pablo; Ok, Yong Sik; Borie, Fernando (Journal of soils and sediments, 2017)
Purpose Copper (Cu) contamination has been increasing in land ecosystems due to economic development activities. Excessive amount of Cu in soils is toxic to both plants and microorganisms. Biochar (BC) is known to immobilize soil Cu. The objectives of this research were to investigate the effects of chicken-manure-derived BC (CMB) on Cu immobilization, and growth of native metallophyte Oenothera picensis in a Cu-contaminated soil. Materials and methods A Cu-contaminated sandy soil (338 mg Cu kg −1 ) was spiked and equilibrated with additional Cu (0, 100, and 500 mg Cu kg −1 ). The spiked soil was then amended with CMB (0, 5, and 10 % w/w ) and incubated for 2 weeks. The metallophyte was grown on these treatments under greenhouse conditions for 3 months. Pore water solutions were collected from the plant pots every 30 days. After the harvest, soil and pore water pH, soil Cu fractions, pore water Cu concentration, soil microbial activity, plant biomass weight, and Cu concentration in plant parts were determined. Results and discussion The CMB increased the pH of soils and soil pore water, and probably also soil major nutrients. It reduced the exchangeable fraction of Cu but increased its organic matter and residual fractions. At the same time, it decreased the Cu concentration in the soil pore water. The CMB increased basal respiration and dehydrogenase activity. The CMB application produced up to three and seven times more root and shoot biomass, respectively. In addition, shoots accumulated lesser Cu than control but roots did more. Plants survived in soil that was spiked with 500 mg Cu kg −1 , only when CMB dose was 10 %. Conclusions The CMB affected the Cu uptake in plant by altering the mobility, bioavailability, and spatial distribution of Cu in soils. The increase in available nutrients and decrease in Cu toxicity facilitated plant growth. The increased microbial activity probably also promoted the plant growth and reduced the Cu bioavailability. Therefore, CMB can be used to remediate Cu-contaminated soils.